FORMAREA COMPETENŢELOR ANTREPRENORIALE DIN PERSPECTIVA ASIGURĂRII CALITĂŢII EDUCAŢIEI - USM ADMIN (Moldova State University, 2009)
The present article reflects upon the analysis of entrepreneurial competencies, determined by the Council of Europe, by the educational structure prism, regarded as the didactic field, socio-economic, the field of knowledge.